Sistem Informasi E-Commerce sebagai Platform Penjualan Barang Fashion dan Aksesoris Berbasis Website - Pasha, Eclesianetha Ayu (Journal of Information System and Computer, 2024)
Web-based E-Commerce Information Systems have become an innovative solution to support buying and selling transactions, especially in the fashion and accessories sector. This study aims to develop an e-commerce platform that facilitates transaction processes with a focus on efficiency, security, and user experience. The system is designed using the Waterfall software development model, encompassing requirements analysis, interface design, implementation, and testing. Utilizing PHP and XAMPP as development tools, the system offers an intuitive interface, robust data integration, and features such as inventory management and seamless checkout processes. The results demonstrate that this platform can enhance operational efficiency for business owners while providing convenience and security for consumers.